One new genus and two new free-living nematode species (Desmodorida, Desmodoridae) from the continental margin of New Zealand, Southwest Pacific Ocean - Leduc, Daniel; Verschelde, Dominick (Zootaxa, 2013)
One new genus and two new species of the family Desmodoridae are described from the upper continental slope of New Zealand, at 350–1240 m water depths. Onepunema gen. n. is characterised by a striated head capsule, small buccal cavity without teeth, and presence of two testes. Onepunema gen. n. can be differentiated from all other genera of the family by the presence of two testes, which is an exception to the holapomorphic character (i.e. monorchic males) of the Desmodoroidea. Onepunema enigmaticum gen. et sp. n. shares characters typical of the subfamilies Spiriniinae (small buccal cavity without distinct teeth) and Desmodorinae (presence of head capsule). Onepunema gen. n. is placed within the Desmodorinae based on the latter trait, which is never found within the Spiriniinae. The type species, Onepunema enigmaticum gen. et sp. n., is characterised by the presence of two laterodorsal and two lateroventral rows of pores with conspicuous ducts, slender pharynx with rounded terminal bulb, presence of two types of cells in intestinal epithelium, and presence of four or five pre-cloacal supplements consisting of thickened areas of cuticle in males. The genus Pseudonchus is recorded for the first time from the deep sea (1240 m water depth) and from the New Zealand region. Pseudonchus virginiae sp. n. is characterised by its stout body, short cephalic setae, monospiral amphideal fovea, short arcuate spicules with capitulum, five regularly-spaced precloacal setae, and short conical tail. A key to all known valid species of the genus Pseudonchus is provided.